Zeolite and deionised zeolite with magnesium in vitro comparative study - Ildikó Szilágyi; Zsuzsanna Czibulya; Attila Csík; Mihály Braun; Csaba Hegedűs (Hungarian Dental Association, 2021)
Examination of the zeolite and magnesium-exchanged zeolite system on human stem cells culture, different viability and ALP activity values at different concentrations provide information on the factors influencing ossification and bone "turnover". The aim of our present work was to investigate the effect of zeolite and magnesium ion-exchanged zeolite concentrations (0.605 mM, 0.325 mM, 0.15 mM Mg-zeolite and zeolite) in an in vitro experimental system on culture medium from wisdom tooth cells (DPSC - dental pulp stem cells) at different sampling times (1, 4, 7 and 14 days). Based on our measurements of viability and alkaline phosphatase activity, both components studied, zeolite and magnesium- ion-exchanged zeolite could be promising components of future medical interventions using artificial tissue culture in several areas. Our experiments showed that Mg-zeolite was more effective.